VARIETY OF GASTROINTESTINAL DUPLICATIONS IN CHILDREN: EXPERIENCE AT TERTIARY CARE HOSPITAL - Perveen, Shazia; Ali, Sajid; Israr, Shumaila (Journal of Ayub Medical College Abbottabad, 2021)
Background: Gastrointestinal duplication is a rare developmental anomaly that can be present anywhere along the GI tract, most often being found in ileum. The purpose of this study is to share our experience in evaluation of the presentation, investigations, management challenges and complications of patients with this very rare condition. Methods: This descriptive case series was conducted at the Department of Paediatric Surgery, National Institute of Child Health Karachi, Pakistan, from April 2018 to October 2019. Data was analysed with regard to age, clinical presentation, investigations, surgical procedures, site and type of lesion, histopathology, complications and outcomes. Results: A total of five patients were managed in one and half year. The patients’ ages ranged from antenatally diagnosed foetus to 12 years old child. New-born who presented with antenatal diagnosis of abdominal cyst turned out to have duodenal duplication cyst. Among other four were thoracoabdominal duplication cyst, gastric duplication, jejunal duplication and ileal duplication, last two presented with perforation. Other presentations were abdominal pain, swelling and vomiting. Diagnosis was made on clinical ground, x-ray of abdomen, ultrasound and computed tomography. All cysts were resected successfully and patients remained asymptomatic till one year follow up except one patient who expired postoperatively due to liver failure. Conclusion: Enteric duplication can present in variety of ways depending on anatomical location. Prompt diagnosis and complete excision of cyst is the aim of treatment. However, these rare types of duplication are a challenge to operating surgeons.